IDT114 : Technical drawing / Faculty of Art and Design - UiTM, Faculty of Art and Design (Universiti Teknologi MARA (UiTM), 2023)
This course involves a careful examination of drafting as a tool of technical communication and for solving graphical problems. Emphases are on development of basic drafting skills, visualization, and solution of spatial problems. This course provides instruction on producing drawings utilizing a computer for products, furniture, interior, transports and more. This course intended to introduce students to basic concepts of Computer-Aided Design, as they will be implementing on the personal computer. It is particularly also intended to meet the needs of students with little or no computer or CAD experience. Depending on background, students will be introduce or will become more skilful on applying manual CAD and also in the computer production such as lettering, notation, geometric constructions, editing tools, drawing organization, multi-view drawings, dimensioning techniques, plotting, auxiliary views, section views, assembly drawings, blocks and other standard drafting procedures also the introduction to solid modelling. Students learn conversion from isometric (a single-angle-view) to orthographic (two or more straight views) and from orthographic to isometric visualization and perspective rendering.